Manisuris ratnagirica Kulkarni et Hemadri New Grass from the Sahyadri Range, Maharashtra State - Kulkarni, B. G.; Hemadri, Koppula (Indian Forester, 1974)
Manisuris ratnagirica Kulkarni et Hemadri-a new grass collected on the plateaus along Ambo-lighat of the Sahyadri ranges in Ratnagiri district, Maharashtra State is described with illustrations. Also, Manisuris goaensis Rolla Roa et Hemadri is recorded for the first time from Maharashtra state, whereas M. mysorensis Jain et Hamadri is recollected from one of its type localities after a lapse of over 70 years.